2010
DOI: 10.1097/wno.0b013e3181ceb483
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of Two Dural Carotid-Cavernous Fistulas Presenting With Optic Neuropathy and Marked Congestive Ophthalmopathy

Abstract: Two patients with dural carotid-cavernous fistulas (CCFs) presented with optic neuropathy and marked congestive ophthalmopathy, including 1 patient with a narrowed anterior chamber angle due to choroidal effusions. Endovascular intervention was planned but deferred for logistic reasons. While the patients awaited the procedures, the clinical features markedly improved, and time-resolved imaging of contrast kinetics (TRICKS) MRA was consistent with closure of the CCFs. These patients serve as a reminder that sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Bujak et al reported 2 cases with optic neuropathy and marked congestive ophthalmopathy as manifestations of CSdAVF. Although these patients did not undergo interventional management, they eventually showed dramatic improvement in symptoms and complete regression of the fistula [11]. This paradoxical worsening of presenting symptoms before spontaneous occlusion may have been the result of increased venous pressure caused by thrombus formation of the affected vein [23,25].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Bujak et al reported 2 cases with optic neuropathy and marked congestive ophthalmopathy as manifestations of CSdAVF. Although these patients did not undergo interventional management, they eventually showed dramatic improvement in symptoms and complete regression of the fistula [11]. This paradoxical worsening of presenting symptoms before spontaneous occlusion may have been the result of increased venous pressure caused by thrombus formation of the affected vein [23,25].…”
Section: Discussionmentioning
confidence: 97%
“…Among the 34 untreated CSdAVF patients, 21 patients (male/female, 7/14; mean age, 59.7 years; median clinical follow-up, 12 months; range, 3-151 months) manifested symptom changes, and 16 underwent follow-up angiography after symptom changes. The median interval of symptom changes was 4 months (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14], and the median time interval from initial angiography to follow-up angiography was 4 months (range, 1-69). On initial digital subtraction angiography (DSA), patients comprised 8 with type I, 1 with type II, and 8 with type III, including 2 with type IIIC, and 2 with type IV.…”
Section: Baseline Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 patients had a preoperative GCS score ranging from [3][4][5]49 patients ranged from 6-9 and 33 patients were greater than 9. The mean preoperative score was 8.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6]10 When standard treatments for elevated ICP are exhausted without any signs of improvement, decompressive craniectomy can be an effective alternative solution.…”
Section: Trauma Introductionmentioning
confidence: 99%